Reading Interest and Mastery of Foreign Absorbing Vocabulary (Minat Baca dan Penguasaan Kosakata Serapan Asing) - Asep Muhyidin (Indonesian Language Education and Literature, 2018)
This study aimed to determine whether there is 1) the relationship between read interest with reading comprehension skill, 2) the relationship between foreign vocabulary mastery with reading comprehension skill, and 3) the relationship between read interest and foreign vocabulary mastery together with reading comprehension skill. This research was conducted at SMA Negeri 4 Kota Serang, February to June 2016. The research method used is survey method with correlation techniques. The population was tenth grade students of SMA Negeri 4 Kota Serang. The sample of 66 people taken by simple random sampling. Instruments to collect data is a test of reading comprehension skill, test of foreign vocabulary mastery, and questionnaire for reading interest. The results of research as follows: 1) there is a positive and significant relationship between read interest with reading comprehension skill; 2) there is a positive and significant relationship between foreign vocabulary mastery with reading comprehension skill; and 3) there is a positive and significant relationship between read interest and foreign vocabulary mastery together with reading comprehension skill.Â Penelitian ini bertujuan untuk membuktikan ada tidaknya (1) hubungan antara minat baca dengan kemampuan membaca pemahaman, (2) hubungan antara penguasaan kosakata serapan asing dengan kemampuan membaca pemahaman, serta (3) hubungan antara minat baca dan penguasaan kosakata serapan asing secara bersama-sama dengan kemampuan membaca pemahaman. Penelitian dilakukan di SMA Negeri 4 Kota Serang, pada bulan Februari sampai dengan Juni 2016. Metode penelitian yang digunakan adalah metode survei dengan teknik korelasional. Populasi adalah siswa kelas X SMA Negeri 4 Kota Serang. Sampel 66 orang yang diambil secara simple random sampling. Instrumen untuk mengumpulkan data adalah tes kemampuan membaca pemahaman, tes kosakata, dan angket minat baca. Hasil penelitian: 1) terdapat hubungan yang positif dan signifikan antara minat baca siswa dengan kemampuan membaca pemahaman; 2) terdapat hubungan yang positif dan signifikan antara penguasaan kosakata serapan asing dengan kemampuan membaca pemahaman; dan 3) terdapat hubungan yang positif dan signifikan antara minat baca dan penguasaan kosakata serapan asing secara bersama-sama dengan kemampuan membaca pemahaman.